MSME Empowerment Program at TPS3R Ngudi Lestari: Alternative Livestock Facilities - Moch Faiz Irwani; Sun Ummi Chonitah Zam Amiroh; Falakhul Azizi; Alifia Shafaradila; Shofia Anisa Firdaus; Hasna’ Febby Nur Adilah; Sri Dara Mahmudin; Puji Lestari (Universitas Kristen Indonesia Toraja, 2024)
Innovation in the livestock sector, especially in terms of providing alternative animal feed, is an urgency that cannot be ignored in Indonesia. This is especially true for small and medium-scale farmers who often face various challenges in maintaining the sustainability of their businesses. Maggots themselves can be used as an alternative means in livestock farming because they can be used as animal feed by residents. This study uses a community-based participatory research (CBPR) approach to identify gaps. CBPR is a collaborative research approach designed to improve the quality of life. This approach involves community members, stakeholders, and stakeholders in the research process. Researchers, and other relevant stakeholders. The results of this study indicate that maggots can be used as an alternative animal feed because they have high protein.